2007
DOI: 10.1590/s1516-18462007000400004
|View full text |Cite
|
Sign up to set email alerts
|

Terapia fonológica: a generalização a itens não utilizados no tratamento (outras palavras)

Abstract: OBJETIVO: verificar a generalização a itens não utilizados no tratamento (outras palavras) obtida em três modelos de terapia em sujeitos com diferentes graus de gravidade do desvio fonológico. MÉTODOS: o grupo pesquisado foi constituído por 21 sujeitos com desvio fonológico, 11 do sexo masculino e 10 do feminino, com média de idade no início do tratamento de 5:7 anos. Os dados da fala foram analisados por meio da avaliação fonológica. Após a realização da análise contrastiva, foi calculado o Percentual de Cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
20
0
12

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 12 publications
11
20
0
12
Order By: Relevance
“…These findings agree with other studies 5,8,13,18,19,27 in which the use of therapeutic approaches improved the subjects' phonological inventory. Authors of other studies 1,27 referred PCC-R increase during intervention, with decrease of phonological disorder severity.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These findings agree with other studies 5,8,13,18,19,27 in which the use of therapeutic approaches improved the subjects' phonological inventory. Authors of other studies 1,27 referred PCC-R increase during intervention, with decrease of phonological disorder severity.…”
Section: Discussionsupporting
confidence: 92%
“…Similar results were found in other studies 2,6,8,15,18,19,27,28 which reported generalization percentage increase with different phonological therapy approaches and consequent reduction of therapy time.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…About the phonemes acquisition, the fact that the EG presented significant increase regarding acquired phonemes agree with studies (7)(8)(9) that verified improvement in relation to the Student's t-test (two independent samples) Acquired phonemes: percentage of correct production higher than 80% (17) Note: PE-1 = first phonological evaluation; PE-2 = second phonological evaluation; SD = standard deviation phonological system acquisition with phonological therapy. Besides, it confirms that the therapeutic intervention is efficient to increase the number of sounds in the phonological system (7,8,13) . The phonemes acquisition for the CG, after the second evaluation (PE-2) refers, mainly, to the partially acquired phonemes.…”
Section: Discussionsupporting
confidence: 52%
“…In general, researches in the area (6)(7)(8)(9)(10)(11)(12)(13)(14)(15) aimed at describing the improvements obtained through the treatment. However, it is important to understand the course of acquisition in which, even without therapy, the child with phonological disorder goes through with the purpose of supplying, or not, their speech difficulties as time passes, evidencing that the changes in the phonological systems, which are stagnant, may occur, without therapy.…”
Section: Introductionmentioning
confidence: 99%